Psychopathological manifestations of endogenous psychoses in remission / intermission state as a predisposal factor to personological transformations (comparative analysis) - Khomitskyi, M. Ye. (Zaporozhye Medical Journal, 2018)
Differential diagnosis of endogenous episodic psychoses is an extremely important task of modern psychiatric theory and practice in view of the existing pathomorphosis of mental illness and tendency of the recent years to steady expansion and transformation of ideas about taxonomy and typology. To make the correct diagnosis at the onset of endogenous illness is a significant factor for adequate and successful further therapeutic and social rehabilitation measures, which determine the medical and social prognosis and the quality of patients’ life. The aim of this study was a comparative analysis of the clinical and psychopathological characteristics of remission states in patients suffering from schizophrenia, schizoaffective disorder (SAD) and affective disorders (AD). Contingents and methods. 49 patients suffering from AD (31 patients were diagnosed with bipolar affective disorder and 18 - with recurrent depressive disorder), 76 patients with diagnosis of schizoaffective disorder and 96 patients – paranoid schizophrenia, episodic type of course were examined on the basis of the Regional Clinical Psychiatric Hospital (Zaporizhzhia). The structure of the disease episodes was characterized by a pronounced affective component in all studied patients. The mandatory inclusion criterion for both groups was the state of clinical remission with psychotic symptoms reduction. The main methods of examination were clinical-catamnestic and clinical-psychopathological as well as medical-statistical analysis. Results. The obtained results allowed to reveal the presence of negative, general and productive disorders in patients with periodic endogenous psychoses in the state of remission, which are related to pathopersonological transformations. Nosologically specific increase in pathopersonological transformations severity was recorded in the AD-SAD-schizophrenia direction. There was a discrepancy between the aforementioned tendency (the increase in psychopathological symptoms severity in the AD-SAD-schizophrenia direction) and some indicators of positive disorders subscale (P4 (Excitement) and P5 (Grandiosity)). The profile of pathopersonological transformations in SAD had the most complex structure in the group of periodic endogenous psychoses. Conclusions. The study of stable pathopersonological transformations of these contingents would help to increase the accuracy of differential diagnosis in the group of periodic endogenous psychoses, leading to enhanced efficiency of the treatment and rehabilitation measures undertaken.